Airing Invisible Stories: Lively Storytelling in Early Childhood Education - Morrow, Ali; Lackner, Astrid; Ibanez, Veronica (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
This paper is an attempt to approach the complexities of interdependent lifeworlds through an engagement with the multiple appearances and becomings of Air. Air’s mysterious unknowability calls forth a sense of deep listening and attunement, including the ways in which elemental and more-than-human communities communicate or encounter one another. Seeking to practice ethical and political pedagogies within contemporary early childhood care and education, the authors orient this paper within a posthumanist theoretical framework while engaging in interdisciplinary collaborations with environmental humanities and postpositivist, poststructural, feminist writings. This paper employs lively storytelling in an attempt to decenter humancentric views and to create the possibility for others to be heard.